Problematyka udostępniania aktów prawnych i orzeczeń w internecie - Chromicka, Dorota (Kwartalnik Prawa Publicznego, 2012)
The rise of information society has increased the significance of saving, storing or publishing information in an electronic form. January 2012 marks the beginning of electronic announcement and publication of normative acts and other forms of legislation. However, it is not clearly stipulated whether court decisions should be made widely available. There arise further doubts related to the means and the scope of their electronic publication. This study aims at presenting the rules of gaining access to normative acts and court decisions on the Internet as a distinct example of access to public information, co-existing with the Public Information Bulletin.